2021
DOI: 10.3390/cancers13246303
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Role and Therapeutic Potential of Extracellular Vesicles

Abstract: Cell–cell communication is an important mechanism in biological processes. Extracellular vesicles (EVs), also referred to as exosomes, microvesicles, and prostasomes, are microvesicles secreted by a variety of cells. EVs are nanometer-scale vesicles composed of a lipid bilayer and contain biological functional molecules, such as microRNAs (miRNAs), mRNAs, and proteins. In this review, “EVs” is used as a comprehensive term for vesicles that are secreted from cells. EV research has been developing over the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 234 publications
0
6
0
1
Order By: Relevance
“…These data also suggest that the suppression of EV release may potentially have an antifibrotic effect. In fact, EVs have been implicated in multiple other conditions including cancers and neurodegenerative diseases (46,47), increasing interest in the therapeutic potential of inhibitors of EV release (48). More specific to fibrosis, Liu et al demonstrated that inhibition of EV release by TGFβ-activated human kidney proximal tubule cells attenuated the activation of interstitial kidney fibroblasts in vitro (49).…”
Section: Discussionmentioning
confidence: 99%
“…These data also suggest that the suppression of EV release may potentially have an antifibrotic effect. In fact, EVs have been implicated in multiple other conditions including cancers and neurodegenerative diseases (46,47), increasing interest in the therapeutic potential of inhibitors of EV release (48). More specific to fibrosis, Liu et al demonstrated that inhibition of EV release by TGFβ-activated human kidney proximal tubule cells attenuated the activation of interstitial kidney fibroblasts in vitro (49).…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular vesicles (EVs) are microscale vesicles composed of lipid bilayers released by various cell types, containing proteins, nucleic acids, lipids, and metabolites (Tominaga, 2021). Since EVs are involved in intercellular signaling, as they are transported and function between host and recipient cells (Xu et al, 2016), EVs are valuable tools for studying cell-cell communication in biological processes, including cancer, autoimmune disease, and neurodegenerative disorder, leading to blood-based biomarkers for early diagnosis disease (Wu et al, 2020; Delpech et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These early endosomes later mature into multivesicular bodies which fuse with the cellular membrane allowing for the release of exosomes to the extracellular space. Microvesicles on the other hand are simply formed through membrane budding [ 10 , 11 ]. Our lab previously identified that tipifarnib has the ability to target exosome biogenesis, the exact mechanism is the topic of this study.…”
Section: Introductionmentioning
confidence: 99%